Efforts To Improve Student Activities And Learning Outcomes On The Material Of Social Conflicts With Learning Methods STAD In Class XI Ips.1 SMA NU Juntinyuat Classroom Action Research - Miftahul Fatah (Cita Konsultindo Research Center, 2023)
One of the efforts to prepare the next generation, both in school and outside of school, is expected to become educated citizens. The purpose of this study is one of the efforts to prepare the next generation, both in school and outside of school, to be expected to become educated citizens. Data collection techniques are carried out by researchers with qualitative data collection techniques. After the implementation of the first cycle of action using the group work method and the question and answer method, there was a positive change with an increase through student abilities. From the results of the implementation of the first cycle, an increase in the level of student understanding in Sociology learning was obtained, namely with an average score of 64 students and students who were declared to have passed as much as 68% while in the second cycle of SOCIOLOGY learning the average score obtained by students was 70 with a graduation percentage of 96%. In cycle II, there are findings, namely judging from the test results, many students are declared passed or successful and seen in the success of student indicators declared to have been successful in achieving the target, so that cycle III is not implemented